2006
DOI: 10.1074/jbc.m604849200
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Early Steps of HIV-1 Replication by SNF5/Ini1

Abstract: The replication cycle of human immunodeficiency virus, type 1 (HIV-1) 4 involves the insertion of a DNA copy of its RNA genome into a chromosome of the host cell. Following retrovirus entry, a large nucleoprotein complex called preintegration complex (PIC) is formed in the cytoplasm with components of the virion core and cellular factors. In addition to viral cDNA, PICs contain several viral proteins: matrix, nucleocapsid, reverse transcriptase, VPR protein, and integrase (IN), which carries out DNA-cutting an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 57 publications
3
35
0
Order By: Relevance
“…The level of cDNA synthesis was maximal at 10 h posttransduction in the three cell lines and decreased subsequently (Fig. 4A), in agreement with a previous report (39) . In control cells treated with zidovudine, the signal was weak, confirming that we were measuring exclusively de novo synthe- (Fig.…”
Section: Transgene Overexpression After Transduction Of Ku-deficient supporting
confidence: 81%
“…The level of cDNA synthesis was maximal at 10 h posttransduction in the three cell lines and decreased subsequently (Fig. 4A), in agreement with a previous report (39) . In control cells treated with zidovudine, the signal was weak, confirming that we were measuring exclusively de novo synthe- (Fig.…”
Section: Transgene Overexpression After Transduction Of Ku-deficient supporting
confidence: 81%
“…Interestingly, we found that two core components of the SWI/SNF ATP-dependent BAF chromatin remodeling complex, SWI/SNF related, matrix associated, Actin dependent Regulator of Chromatin, subfamily D1 (SMARCD1), member 1 BAF60, and SMARCB1 (SNF5/INI1) were down-regulated two hours following vorinostat (red arrowhead Figure 6B ). SNF 5/INI1 is an essential HIV host cell factor involved in the integration of viral cDNA into active genes [30]. Its expression interferes with viral replication and knockdown has been shown to increase expression of HIV 2LTR circles, a dead end product of HIV replication [30].…”
Section: Resultsmentioning
confidence: 99%
“…SNF 5/INI1 is an essential HIV host cell factor involved in the integration of viral cDNA into active genes [30]. Its expression interferes with viral replication and knockdown has been shown to increase expression of HIV 2LTR circles, a dead end product of HIV replication [30]. In addition, recent studies suggest that loss of SNF5 activity results in the disruption of nucleosome occupancy at transcriptional start sites (TSS) of gene promoters resulting in the upregulation of E2F target genes associated with cell cycle and proliferation [28].…”
Section: Resultsmentioning
confidence: 99%
“…Alteration of host cell components of RTC/PIC may affect the formation or the stability of these complexes and thereby have a negative impact on viral replication (22,31). We therefore measured the expression of host factors associated with the RTC/PIC that might interfere with either reverse transcription or integration, including lens epithelium-derived growth factor (LEDGF)/p75 (12,40), integrase interactor 1 (Ini1) (34,45), barrier-to-autointegration factor (BAF) (39), Gemin2 (27), and p21 (81) stimulation induced no significant change in the expression of Ini1, Gemin2, or BAF relative to control macrophages (Fig. 2C).…”
Section: Fc␥r-mediated Restriction Of Hiv-1 Replication Does Not Depementioning
confidence: 99%